Comparison and environmental controls of soil respiration in primary and secondary dry dipterocarp forests in Thailand - Tammadid, Wittanan; Sangkachai, Bantita; Chanonmuang, Phuvasa; Chidthaisong, Amnat; Hanpattanakit, Phongthep (Frontiers in Forests and Global Change, 2024)
Soil respiration (Rs) in forest ecosystems is an important process in the global carbon cycle. The unbalanced use of forest natural resources and deforestation in the past have resulted in changes in forest structure, tree growth, and the release of carbon dioxide (CO2) emissions from Rs. Understanding Rs in both primary and secondary forests plays a crucial role in the global carbon cycle. Therefore, the purpose of this study was to estimate and compare Rs in primary dry dipterocarp forests (PDDF) and secondary dry dipterocarp forests (SDDF) in Thailand, in relation to diurnal and seasonal variations in environmental variables (air and soil temperatures, and soil moisture). CO2 flux was measured continuously from March 2019 to February 2020 in the PDDF and SDDF sites in the Nakhon Ratchasima and Ratchaburi provinces of Thailand. Using the soil gradient method, CO2 probes were employed to measure average CO2 concentrations from Rs every minute in the both sites. Additionally, air and soil temperatures and soil moisture were measured continuously to analyze the correlation between Rs and environmental variables. The average annual soil respiration rate in PDDF and SDDF were 8.16 and 8.83 tons C ha−1 yr−1, respectively. The diurnal variation of Rs in both sites changed according to air and soil temperatures. The monthly variation of the average Rs was lower in the PDDF site than in the SDDF site. Soil moisture and soil temperature were significantly correlated with the monthly variation of Rs in both sites. Rs in the PDDF and SDDF sites exhibited high emissions during the wet season, accounting for ~61 and 56% of the total annual emissions, respectively. The results indicated that soil and air temperatures were the main drivers of diurnal variation, while the combination of soil moisture and soil and air temperatures determined the seasonal variations. Additionally, litterfall production was the main carbon substrate promoting soil respiration in the SDDF site, as litterfall production was significantly lower in the PDDF site (5.32 tons dry matter ha−1 yr−1) than in the SDDF site (10.49 tons dry matter ha−1 yr−1).